Two cases of erosive oral lichen planus with autoantibodies to desmoglein 3. Issue 11 (26th July 2016) - Muramatsu, Ken; Nishie, Wataru; Natsuga, Ken; Fujita, Yasuyuki; Iwata, Hiroaki; Yamada, Tamaki; Yamashita, Emi; Asaka, Takuya; Shimizu, Hiroshi
Abstract: Oral lichen planus (OLP) is a chronic inflammatory disorder of the oral mucosa of unknown etiology. Clinically, the erosive type of OLP (erosive OLP) can show features similar to those of pemphigus vulgaris (PV), an autoimmune blistering disorder in which desmoglein (Dsg)3 is targeted. In addition to clinical and histopathological findings, immunological studies, including direct immunofluorescence (IF), indirect IF and enzyme‐linked immunosorbent assay (ELISA) that detect autoantibodies to Dsg3, are helpful in differentiating erosive OLP from PV. Here, we show two cases of erosive OLP with autoantibodies to Dsg3. Patient 1 was a 68‐year‐old woman with chronic erosions of the oral mucosa, in which elevated levels of immunoglobulin (Ig)G autoantibodies to Dsg1 and Dsg3 were detected by ELISA. Patient 2 was an 85‐year‐old woman with white striae with erosions on the lateral sides of the buccal mucosa with elevated levels of IgG autoantibodies to Dsg3 detected by ELISA. Histopathological findings from both cases showed lichenoid dermatitis, and both direct and indirect IF showed no tissue‐bound IgG autoantibodies. From these findings, the diagnosis of erosive OLP was made. Immunological assays revealed both cases to have IgG‐directing calcium‐independent linear epitopes on Dsg3, which are suggestive of non‐pathogenic autoantibodies. In addition, autoantibodies to Dsg3 in patient 2 reacted with a prosequence‐possessing precursor form of Dsg3 but not with the mature form of the molecule. The present study suggests that erosive OLP may develop anti‐Dsg3 autoantibodies, which should be carefully assessed.